Cover Image. Issue 2 (20th April 2020) - Unknown
Abstract : POLYMORPHISM The conformation of polymer chains and the mode of packing are used in the classification of polymorphism. Particular polymorphic forms can be obtained by varying crystallization conditions. This special issue of Polymer Crystallization, guest‐edited by Prof. Shichun Jiang and Prof. Pengju Pan, showcases the articles dedicated to studying the polymorphism phenomena in polymers, crucial for potential polymer applications and processing. Abstract : POLYMORPHISM The conformation of polymer chains and the mode of packing are used in the classification of polymorphism. Particular polymorphic forms can be obtained by varying crystallization conditions. This special issue of Polymer Crystallization, guest‐edited by Prof. Shichun Jiang and Prof. Pengju Pan, showcases the articles dedicated to studying the polymorphism phenomena in polymers, crucial for potential polymer applications and processing.